2019
DOI: 10.21079/11681/32298
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of airfield damage repair methods for extreme cold temperatures

Abstract: To address the need for expedient repair solutions for paved runways in cold environments, airfield damage repair Rapid Airfield Damage Recovery (RADR) materials were tested at temperatures down to-40 ºF. New materials and methods were developed to fill the identified performance gaps for conventional RADR materials. Simulated crater repairs were performed at-20 and-40 ºF. Folded fiber glass panels and hinges met the published tensile strength, but did not meet the required flexural strength. Fiberglass-reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…thick slush. 1 For a given snow density, we have found that, although taking longer to freeze-up, cellulous-treated snow reaches a notably higher ultimate strength. In several of the gabions, cellulous was scooped from drums and spread over the top of the stockpiled snow.…”
Section: Tablementioning
confidence: 73%
See 1 more Smart Citation
“…thick slush. 1 For a given snow density, we have found that, although taking longer to freeze-up, cellulous-treated snow reaches a notably higher ultimate strength. In several of the gabions, cellulous was scooped from drums and spread over the top of the stockpiled snow.…”
Section: Tablementioning
confidence: 73%
“…Except for the 5.56 mm rounds, penetration after 48 h into celluloustreated snow was greater than for either 24/18-hr or 48-hr gabions without cellulous. This is likely explained by our previous discovery [1] that snow mixed with cellulous sinters more slowly that untreated snow. Immediately after construction, the snow in each gabion was warmer than the surrounding, undisturbed snow, both because of frictional heating during the snowblowing process and the addition of water or water and cellulous.…”
Section: Ballistics Test Resultsmentioning
confidence: 89%
“…When snow in its natural state does not contain enough moisture content to allow good compaction (and subsequent intergranular bond formation), manual wetting can add to the range of application conditions. Laboratory tests (Asenath-Smith et al 2019) show that frozen slush can be an expedient, high-performing crater repair material. Slush, a mixture of natural snow and water, works best for cavity repair in areas where frost enters the ground and persists throughout much of a winter.…”
Section: Snow As a Patching Materialsmentioning
confidence: 99%
“…Like frozen slush, cellulose-reinforced slurry (water-snow mixture) should be used when conditions are less than 25°F but greater than −40°F. The advantages to using the cellulose as an additive is that uniaxial compressive tests indicate about a 20% increase in strength over frozen slush by itself (Asenath-Smith et. al 2019).…”
Section: Snow As a Patching Materialsmentioning
confidence: 99%
See 1 more Smart Citation